A Two-Stage Approach to Domain Adaptation for Statistical Classifiers - JIANG, Jing (Institutional Knowledge at Singapore Management University, 2007)
In this paper, we consider the problem of adapting statistical classifiers trained from some source domains where labeled examples are available to a target domain where no labeled example is available. One characteristic of such a domain adaptation problem is that the examples in the source domains and the target domain are known to follow different distributions. Thus a regular classification method would tend to overfit the source domains. We present a two-stage approach to domain adaptation, where at the first